The association between low blood lead levels and the prevalence of prehypertension among nonhypertensive adults in Korea. Issue 5 (28th April 2016) - Lee, Wanhyung; Yoon, Jin‐ha; Roh, Jaehoon; Lee, Seunghyun; Seok, Hongdeok; Lee, June‐hee; Jung, Pil Kyun; Rhie, Jeongbae; Won, Jong‐uk
Abstract : Objectives: Low‐level lead exposure has been associated with increases in blood pressure (BP) and impairment of the cardiovascular system. Prehypertension is not categorized as a disease currently; however, individuals with untreated prehypertension are known to be at increased risk of progression to hypertension and mortality caused by cardiovascular disease. We investigated the association between blood lead levels below the threshold for the harmful effects of lead and the prevalence of prehypertension in Korean adults. Methods: A total of 8, 493 participants (3, 945 men and 4, 548 women) were included in the current analysis, using data from the fourth, fifth, and sixth Korean National Health and Nutrition Examination Survey (KNHANES) in 2007–2013. Blood analysis, self‐report questionnaires, and physical examinations were used to assess blood lead levels, BP, and medical history. Odds ratios (OR) and 95% confidence intervals (95% CI) for prehypertension were calculated using multiple logistic regression models. Results: Compared to the first quartile (Q1) blood lead level (0.206–1.539 μg/dl), the ORs (95% CI) were 1.24 (1.04–1.48) in Q2, (1.540–2.056 μg/dl), 1.27 (1.06–1.52) in Q3, (2.057–2.716 μg/dl), and 1.30 (1.07–1.60) in Q4 (2.717–24.532 μg/dl) for the prevalence of prehypertension after adjusting for age, sex, morbidity status, socioeconomic status, and health behavioral variables. Conclusions: Our large, cross‐sectional, nationwide study revealed that blood lead levels below the threshold for the harmful effects of lead were significantly associated with prehypertension. Am. J. Hum. Biol. 28:729–735, 2016. © 2016 Wiley Periodicals, Inc.